Two new peculiar species of Neotropical Brachypogon Kieffer (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2013)
Brachypogon biradialis from southern Argentina and Chile and Brachypogon tico from Costa Rica, are described and illustrated from female specimens. They are provisionally placed in the genus Brachypogon although not exactly fitting in any of the already recognized subgenera of this genus.